2017
DOI: 10.4236/ojn.2017.77065
|View full text |Cite
|
Sign up to set email alerts
|

Older People’s Lived Experiences with Participation in Shareholding Networks for the Care of Older People in Rural Areas of Thailand: A Phenomenological Hermeneutic Study

Abstract: Background: Older people participating in shareholding networks are exposed to diverse situations, which may be associated with dignity. Aims: This study aimed to illuminate the meaning of lived experiences when participating in shareholding networks for the care of older people in rural areas. Methods: This qualitative study is based on individual interviews. Ten older Thai persons with at least 12 months of lived experiences participating in shareholding networks for older people in rural areas were intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
(31 reference statements)
1
3
0
Order By: Relevance
“…Regarding this issue, it is therefore necessary to provide meaningful activities for older adults. This is in line with what Voraroon et al [28] found that older persons felt valued if having meaningful duties assigned by the staff when they participated in activities, and were bored, disinterested and frustrated when the activities were meaningless, without duty, and did not match their needs. Good opportunities took into account both external and internal aspects, which are closely interwoven.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding this issue, it is therefore necessary to provide meaningful activities for older adults. This is in line with what Voraroon et al [28] found that older persons felt valued if having meaningful duties assigned by the staff when they participated in activities, and were bored, disinterested and frustrated when the activities were meaningless, without duty, and did not match their needs. Good opportunities took into account both external and internal aspects, which are closely interwoven.…”
Section: Discussionsupporting
confidence: 89%
“…This is different than being involved in leisure and social activities with regard to active ageing as described in Stenner et al [ 17 ]. According to Voraroon et al [ 22 ], older persons felt valued if they had meaningful duties assigned by the staff when they participated in activities, and they were bored, disinterested and frustrated when the activities were meaningless, without duty, and did not match their needs. Regarding this issue, it is therefore necessary to provide meaningful activities for older adults.…”
Section: Discussionmentioning
confidence: 99%
“…According to the informants, participating in the community events made them feel more part of the community and like they were contributing to the community. They discussed how vital it is to always encourage other aged people to take part in the events so that they do not feel isolated (32) The fth theme describes health-related problems. This study revealed that old-age people suffer from a variety of medical conditions, including generalized bodily symptoms, vision and hearing impairment, arthritis, urinary incontinence, diabetes, hypertension, cardiac disorders, and the like.…”
Section: Discussionmentioning
confidence: 99%